Finite-distance gravitational deflection of massive particles by a rotating black hole in loop quantum gravity - Huang, Yang; Cao, Zhoujian (The European physical journal. C, Particles and fields, 2023)
A rotating black hole in loop quantum gravity was constructed by Brahma, Chen, and Yeom based on a nonrotating counterpart using the revised Newman–Janis algorithm recently. For such spacetime, we investigate the weak gravitational deflection of massive particles to explore observational effects of the quantum correction. The purpose of this article is twofold. First, for Gibbons–Werner (GW) method, a geometric approach computing the deflection angle of particles in curved spacetimes, we refine its calculation and obtain a simplified formula. Second, by using GW method and our new formula, we work out the finite-distance weak deflection angle of massive particles for the rotating black hole in loop quantum gravity obtained by Brahma et al. An analysis to our result reveals the repulsive effect of the quantum correction to particles. What’s more, an observational constraint on the quantum parameter is obtained in solar system.